Effect Of Rainfall Rate And Visibility On Free Space Optical Communications In Malaysian Environment - Sheikh Naimullah, Bibi Sarpinah (2004)

(untitled)
Rare usage of Free Space Optical (FSO) communications in Malaysia might be related to environmental factors. Unguided beam is also known as free space optics technology or ‘optical wireless’ or ‘infrared broadband’. This project explores the propagation of point-to-point FSO due to weather conditions. Weather severity has detrimental impact on FSO transmission performance. The impact could result in insufficient quality of transmission and communication failure. Therefore FSO implementation requires thorough study of local weather patterns. By studying the local weather pattern, scattering coefficient and atmospheric attenuation could be derived to determine weather severity in this area. This information could help in predicting possible impact on data transmission quality and transmission interference system operation. In addition, FSO system design could be improved and altered to overcome possible interference and optimize system operation.This study is focused on the effect of rain and haze in Subang Airport. The Climate Division of Meteorological Department, Petaling Jaya branch, provided the data on rain and haze, which were collected hourly throughout year 2000. The rain data, which were collected in mm/hr, are categorized into three groups: heavy rainfall, moderate rainfall and light rainfall. The haze data was collected based on visibility distance in km. The visibility on hazy days is categorized into low visibility and average visibility. The non-selective scattering contributed dominant loss on rainy days and Mie scattering on hazy days. The non-selective scattering is wavelength independent and Mie scattering is wavelength dependent. The wavelength of 1550nm is selected because it is not harmful to the human eyes, not aggressive to the environment and contributes to better performances. The scattering coefficient and atmospheric attenuation for rain and hazy days are determined by using Stroke Law and Beer’s Law. The atmospheric attenuation due to scattering coefficient has greater effect during hazy days than rainy days. From the result analysis, using small beam divergence, small transmitter aperture, larger receiver aperture and short link distance can optimize the FSO system transmission.